ANALISIS KEMAMPUAN MULTIREPRESENTASI SISWA BERDASARKAN GAYA BELAJAR VAK MATERI SUHU DAN KALOR - Chori'ah, Siti Mariatul; Hadi, Wiwin Puspita; Wulandari, Ana Yuniasti Retno; Putra, Dwi Bagus Rendy Astid; Sutarja, Maria Chandra (Natural Science Education Research, 2023)
Multi-representational ability is an important skill for students to have. This study aims to determine students' multi-representational abilities in terms of VAK learning styles on temperature and heat material. This is a mixed-methods research with a sequential explanatory design. This research was conducted at MTs Negeri Bangkalan with a purposive sampling technique. The samples used were from classes VII A and VII B, totaling 45 students. Data collection were carried out by providing VAK learning style questionnaire instruments, multi-representation ability tests, and interview guidelines. Based on the results of the study, it can be concluded that: (1) there are 18 students who have a visual learning style; 14 students have an auditory learning style; and 13 students have a kinesthetic learning style. (2) students' multi-representation abilities based on the VAK learning style are in the medium category. (3) visual students are dominant in verbal representation, kinesthetic students are dominant in symbolic representation, and in visual representation the three learning styles have an average that is not too far away. Students' multi-representational abilities are influenced by differences in student learning styles related to differences in students' understanding of concepts